The frequency of maternal morbidity: A systematic review of systematic reviews. (23rd May 2018) - Gon, Giorgia; Leite, Andreia; Calvert, Clara; Woodd, Susannah; Graham, Wendy J.; Filippi, Veronique
Abstract: Background: Estimates of the burden of maternal morbidity are patchy. Objective: To conduct a systematic review of systematic reviews of maternal conditions to: (1) make available the most up‐to‐date frequency estimates; (2) identify which conditions do not have reliable estimates; and (3) scrutinize the quality of the available reviews. Search strategy: We searched Embase, MEDLINE, and CINAHL, combining terms for pregnancy, frequency (e.g. prevalence, incidence), publication type, and specific terms for each of 121 conditions. Selection criteria: We included peer‐reviewed systematic reviews aiming to estimate the frequency of at least one of the conditions in WHO's list of maternal morbidities, with estimates from at least two countries. Data collection and analysis: We present the frequency estimates with their uncertainty bounds by condition, region, and pregnancy/postpartum period. We also assess and present information on the quality of the systematic reviews. Main results: Out of 11 930 found, 48 reviews were selected and one more was added. From 49 reviews we extracted 34 direct and 60 indirect frequency estimates covering 35 conditions. No review was available for 71% of the conditions on the WHO list. The extracted estimates show substantial maternal morbidity, spanning the time before and beyond childbirth. There were several gaps in the quality of the reviews. Notably, one‐third of the estimates were based only on facility‐based studies. Conclusions: Good‐quality systematic reviews are needed for several conditions, as a research priority. Abstract : This study highlights that substantial maternal morbidity occurs along the pregnancy–postpartum continuum, and that conducting quality systematic reviews is a priority research gap.